Neoconservative Politics and Mobilizations in the Pandemic Context: the Case of Costa Rica - Arguedas Ramírez, Gabriela (2022)
The pandemic of the SARS-CoV-2 virus that produces the disease COVID-19 has generated, since the end of 2019, a concatenation of crises that ranges from basic aspects of public health and the economy, politics, gender, ethnic-racial, and migratory issues, to the cultural industry, sports, and education. Costa Rica has not escaped these problems, and both the population and the government have had to face them in a climate particularly vitiated by the social and political polarization that the country has suffered in the last decades which has directly affected the communicative legitimacy of the central government to face the pandemic and its repercussions.